Polymerase ɛ (POLE) mutations in endometrial cancer: Clinical outcomes and implications for Lynch syndrome testing. Issue 3 (15th September 2014) - Billingsley, Caroline C.; Cohn, David E.; Mutch, David G.; Stephens, Julie A.; Suarez, Adrian A.; Goodfellow, Paul J.
<x xml:space="preserve">Abstract</x> BACKGROUND DNA polymerase ɛ (POLE) exonuclease domain mutations characterize a subtype of endometrial cancer (EC) with a markedly increased somatic mutational burden. POLE‐mutant tumors were described as a molecular subtype with improved progression‐free survival by The Cancer Genome Atlas. In this study, the frequency, spectrum, prognostic significance, and potential clinical application of POLE mutations were investigated in patients with endometrioid EC. METHODS Polymerase chain reaction amplification and Sanger sequencing were used to test for POLE mutations in 544 tumors. Correlations between demographic, survival, clinicopathologic, and molecular features were investigated. Statistical tests were 2‐sided. RESULTS Thirty POLE mutations (5.6%) were identified. Mutations were associated with younger age (<60 years; P=.001). POLE mutations were detected in tumors with microsatellite stability (MSS) and microsatellite instability (MSI) at similar frequencies (5.9% and 5.2%, respectively) and were most common in tumors with MSI that lacked mutL homolog 1 (MLH1) methylation (P<.001). There was no association with progression‐free survival (hazard ratio, 0.22; P=.127). CONCLUSIONS The discovery that mutations occur with equal frequency in MSS and MSI tumors and are most frequent in MSI tumors lacking MLH1 methylation has implications for Lynch syndrome screening and mutation testing. The current results indicate that POLE mutations are associated with somatic mutation in DNA mismatch repair genes in a subset of tumors. The absence of an association between POLE mutation and progression‐free survival indicates that POLE mutation status is unlikely to be a clinically useful prognostic marker. However, POLE testing in MSI ECs could serve as a marker of somatic disease origin. Therefore, POLE tumor testing may be a valuable exclusionary criterion for Lynch syndrome gene testing. Cancer 2015;121:386–394. © 2014 American Cancer Society.